1996
DOI: 10.1093/ajcn/63.3.348
|View full text |Cite
|
Sign up to set email alerts
|

Zinc absorption and intestinal losses of endogenous zinc in young Chinese women with marginal zinc intakes

Abstract: The objective of this study was to determine fractional absorption of exogenous zinc and intestinal excretion of endogenous zinc in women of childbearing age whose habitual dietary zinc intake was marginal. The target population (L group) comprised residents of a remote farming village in northeast China and the control subjects (M group) were residents of Beijing. Mean (+/-SE) calculated dietary zinc intakes were 5.2 +/- 0.2 and 8.1 +/- 0.2 mg/d, respectively. The phytate-zinc molar ratio in the diet of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
1
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(83 citation statements)
references
References 16 publications
5
72
1
5
Order By: Relevance
“…Reducing EFZ is believed to be a homeostatic control mechanism to conserve zinc (2,20). The EFZ of 1.68 Ϯ 1.06 mg/d from young Malawian children of this study is greater and has more variability than that seen in studies from more developed settings, where EFZ was found to be 0.99 Ϯ 0.40 mg/d in US children aged 1-4 y (3), 1.08 Ϯ 0.62 mg/d in US girls aged 9 -14 y (6), and 0.66 Ϯ 0.23 mg/d in Chinese children aged 1.5-2 y (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing EFZ is believed to be a homeostatic control mechanism to conserve zinc (2,20). The EFZ of 1.68 Ϯ 1.06 mg/d from young Malawian children of this study is greater and has more variability than that seen in studies from more developed settings, where EFZ was found to be 0.99 Ϯ 0.40 mg/d in US children aged 1-4 y (3), 1.08 Ϯ 0.62 mg/d in US girls aged 9 -14 y (6), and 0.66 Ϯ 0.23 mg/d in Chinese children aged 1.5-2 y (5).…”
Section: Discussionmentioning
confidence: 99%
“…Zinc retention in humans is not simply determined by the amount of dietary zinc consumed but also by reabsorption of endogenous zinc secreted into the small intestine. The reabsorption of endogenous zinc from the gut is believed to be a mechanism by which zinc homeostasis is maintained (2). The dual zinc stable isotope test involves administration of different zinc stable isotopes orally and i.v.…”
mentioning
confidence: 99%
“…Applying a factorial approach, IOM (2001) determined an additional requirement of 2.7 mg/day, considering the highest average daily rate of zinc accumulation by maternal and fetal tissues of 0.73 mg observed during the fourth quarter of pregnancy (Swanson and King, 1987), and an estimated average FAZ of 0.27 (Turnlund et al, 1991;Hunt J et al, 1992;Sian et al, 1996;Fung et al, 1997;Hunt et al, 1998;Miller et al, 1998). EARs of 10 mg/day for pregnant adolescents aged 14-18 years and of 9.5 mg/day for pregnant women were derived, and RDAs were set at 12 mg/day and 11 mg/day, respectively, by adding twice the CV of 10 % to the EARs and rounding to the nearest 1 mg.…”
Section: Pregnancymentioning
confidence: 99%
“…It may be that this very weak correlation is indicative of the fact that our subjects had adequate Zn status and thus Zn absorption was not affected by this status. Effectively, Zn absorption is expected to be affected in high or low Zn status where the absorption is modulated to maintain Zn status in narrow values (Johnson et al, 1993;Sian et al, 1996). Moreover, Zn absorption was not significantly correlated with any of Fe or Cu status measured in this study; Fe or Cu status also appeared to be adequate in our subjects.…”
Section: Discussionmentioning
confidence: 50%